Fan Nation: Harnessing Fandoms For Political Participation - Celerio, Pauline Jane; Cruz, Mariella Roselle R; Layco, Hydie D.R; Samson, Glenn Pierre C (2015)
In the Philippines, schoolchildren consider celebrities as heroes. During elections, adults elect actors-turnedpoliticians in public office. Former artist Joseph Estrada, for instance, is now mayor of Manila after having been senator, Vice President, and President of the country. Boxing champion Manny Pacquiao, meanwhile, is now in congress representing his home province, Sarangani. Currently, two of the icons being heavily marketed by the country’s largest media conglomerate are comedian Vice Ganda and the romantic tandem of Daniel Padilla and Kathryn Bernardo, dubbed as KathNiel, which both target the youth segment. The three personalities appear in television shows every day and have Facebook pages that have now garnered more than 12 million and 890,000 ‘likes’, respectively.